Islamic school with digital culture in era society 5.0 - Nadifa, Milatun; Ambarwati, Rika Dwi (CAHAYA PENDIDIKAN, 2024)
The era of Society 5.0 presents challenges and opportunities for schools to adopt a digital culture. Challenges involve disparities in internet access and technology among students, limited educator competence, and lack of infrastructure in schools. This research aims to provide solutions by formulating concrete steps. The method used is a literature review from various sources. Based on the results of research from several literatures, conclusions can be drawn about concrete steps that can be used as guidelines for educational institutions, especially Islamic nuanced schools in facing the digital revolution without losing the roots of Islamic values that become their true identity, namely: (1) A holistic curriculum that integrates Islamic values with digital culture, (2) Teacher training to master technology and understand Islamic values, (3) Creating a technology-enabled school environment. It is hoped that the results of this research will be a valuable guide for educational institutions in facing the digital revolution. Practical implications include curriculum development, teacher training, and the creation of a conducive school environment. Further research can explore the effectiveness of curriculum implementation and character building as well as more effective training strategies for teachers.